1989
DOI: 10.1002/eji.1830191223
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin levels and naturally occurring antibodies against carbohydrate antigens in germ‐free BALB/c mice fed chemically defined ultrafiltered diet

Abstract: This study investigates the influence of exogenous antigenic stimulation on the serum immunoglobulin levels and the levels of circulating natural antibodies against carbohydrate antigens. Thus, BALB/c mice, raised in a germ-free environment and fed a chemically defined, ultrafiltered diet (GF-CD), were employed. These mice had normal serum IgM levels, but IgG and IgA levels were approximately 5% of conventionally reared littermates. The concentrations of all four IgG isotypes were equally low. The variable par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 23 publications
(10 reference statements)
6
87
1
Order By: Relevance
“…In support of the concept that B-1 B cells generate this subset is the extensive previous analysis of these cells demonstrating that they produce a large repertoire of low-affinity self-reactive Abs that result from positive selection during B-1 cell development (14,(42)(43)(44). If CR2/CR1 coreceptor function on B-1 B cells is required for the efficient recognition of a critical self Ag that is either identical to, or antigenically related to, the neoantigen revealed on ischemic tissue, this could, in principle, explain our findings relative to the lack of development of this subset of Abs.…”
Section: Discussionmentioning
confidence: 91%
“…In support of the concept that B-1 B cells generate this subset is the extensive previous analysis of these cells demonstrating that they produce a large repertoire of low-affinity self-reactive Abs that result from positive selection during B-1 cell development (14,(42)(43)(44). If CR2/CR1 coreceptor function on B-1 B cells is required for the efficient recognition of a critical self Ag that is either identical to, or antigenically related to, the neoantigen revealed on ischemic tissue, this could, in principle, explain our findings relative to the lack of development of this subset of Abs.…”
Section: Discussionmentioning
confidence: 91%
“…Germ-free mice show reduced numbers of lamina propria CD4 + T cells, IgA-producing B cells, and intraepithelial lymphocytes (55,56), and MLNs and spleens are smaller and less cellular (57). This indicates that commensal bacteria play a crucial role in the maturation of the mucosal immune system during postnatal development.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, natural Abs are independent of internal or external stimuli, whereas genetic differences seem to influence their titres. 33,34 show for example spontaneous reactivity to double-stranded DNA, a self-Ag in murine lupus. 15,36,37 Indeed, when we separated the splenic B cells from naive DBA/1 mice into FO and MZ B cells, we found that the majority of IgG anti-CII AFCs belonged to the MZ B-cell population, and after CII immunization the MZ B cells were the first to significantly expand.…”
Section: Discussionmentioning
confidence: 99%